Sejenak Program (Sigedang Educational Exploration For Children) As An Effort to Minimize Gadget Use In Sigedang Village Children Based On Outdoor Learning - kwee, saniayuen; Ihsanuddin, Iman Ahmad; Afkar, Muhammad Rafi Dzaki; Nisaa, Refa Nahdhatun; Emilia, Miranda; Fajriyah, Nurul (Sentra Kekayaan Intelektual dan Inovasi Teknologi (INOTEK) Universitas Sains Al-Qur'an, 2024)
Excessive use of gadgets in children has become a serious concern in modern society, including in Sigedang Village. To overcome this problem, the SEJENAK Program (Sigedang Edukasi Jelajah Anak) was initiated as an innovative solution that combines education and nature games. This program aims to reduce children's dependence on gadgets by inviting them to participate in various outdoor activities that are educational and fun. Through a nature-based approach, children are invited to learn and play in an environment that supports their physical and mental development. The results of this program showed a significant decrease in the use of gadgets as well as an increase in children's involvement in educational and recreational activities in nature. The SEJENAK program also plays a role in increasing public awareness about the importance of education and outdoor activities for children's development. In addition, the SEJENAK Program also involves the active role of parents and the community in supporting children's development. By holding various workshops and training sessions, parents are given an understanding of the negative impact of excessive use of gadgets and the importance of encouraging children to interact with nature. The local community is involved in this activity, creating a supportive and collaborative environment. Activities such as planting trees, raising animals, and traditional games not only enrich children's experiences but also strengthen social bonds within the community. The program has received positive responses from parents and teachers, who report improved quality of children's interactions, both with peers and with the surrounding environment. Thus, the SEJENAK Program not only focuses on reducing the use of gadgets, but also on building the character of children who are more concerned and sustainable towards nature.